2006
DOI: 10.1007/s11575-006-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of tacit knowledge in China: An empirical analysis of the ‘supplier-side individual level’ and ‘recipient-side’ factors

Abstract: ■ This study examines the impact of 'supplier-side individual level' factors pertaining to foreign expatriates, e.g., individual embeddedness and motivation, as well as a number of recipient-side variables, on tacit knowledge acquisition by Chinese firms through joint ventures.■ Results indicate that individual embeddedness of foreign expatriates, and recipient-side variables such as recipient's collaborativeness, its readiness, and the comprehensiveness of its acquisition methods play critical roles in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 58 publications
6
57
1
1
Order By: Relevance
“…RCOL is closely related to the recipient's learning intent (competitive vs. collaborative intent). The technology recipient firm's willingness to establish a mutually beneficial and collaborative relationship requires the recipient firm's honest intention to create common benefits for both JV partners (Yin and Bao, 2006). Studies on inter OL have suggested that cooperative/collective learning encourages the alliance partners to work together by sharing their knowledge, benefit each other's complementarities and provide mutual opportunities to extract potential synergies between their respective competencies (Doz, 1996;Geringer, 1991).…”
Section: Technology Recipient Characteristics and Degree Of Technologmentioning
confidence: 99%
See 4 more Smart Citations
“…RCOL is closely related to the recipient's learning intent (competitive vs. collaborative intent). The technology recipient firm's willingness to establish a mutually beneficial and collaborative relationship requires the recipient firm's honest intention to create common benefits for both JV partners (Yin and Bao, 2006). Studies on inter OL have suggested that cooperative/collective learning encourages the alliance partners to work together by sharing their knowledge, benefit each other's complementarities and provide mutual opportunities to extract potential synergies between their respective competencies (Doz, 1996;Geringer, 1991).…”
Section: Technology Recipient Characteristics and Degree Of Technologmentioning
confidence: 99%
“…This study measures RCOL in terms of the local partner firms' learning intent and their collaborative attitudes by using a five (5) items scale in terms of 1) the local partner's learning objective, 2) the local partner's desire, determination and will to learn from foreign partner, 3) the technology-recipient's willingness to allow foreign partner to inspect and monitor the use of knowledge acquired from JV, 4) the local partner's commitment not to compete directly with the foreign partner in the future, and 5) the local partner's commitment in sharing with the foreign partner the benefits of the critical knowledge acquired from the JV (Yin and Bao, 2006;Thuc Anh et al, 2006;Hamel, 1991;Simonin, 2004). The Cronbach Alpha for RCOL was higher (0.92) than Yin and Bao's (2006) Cronbach Alpha (0.71).…”
Section: Recipient Collaborativeness (Rcol)mentioning
confidence: 99%
See 3 more Smart Citations